A Comparison of Personality, Life Events, Comorbidity, and Health in Monozygotic Twins Discordant for Anorexia Nervosa. (24th May 2017) - Thornton, Laura M.; Trace, Sara E.; Brownley, Kimberly A.; Ålgars, Monica; Mazzeo, Suzanne E.; Bergin, Jocilyn E.; Maxwell, Millie; Lichtenstein, Paul; Pedersen, Nancy L.; Bulik, Cynthia M.
Abstract : Genetic and environmental factors contribute to the etiology of anorexia nervosa (AN). The co-twin control design is one of the most powerful methods available to evaluate environmental factors that could contribute to differences between monozygotic (MZ) twins who are discordant for AN. Using available data from a unique and rare sample of 22 Swedish female MZ pairs discordant for AN, we compared personality, life events, comorbidity, and health factors. Twins with AN had significantly higher perfectionism scores than unaffected co-twins and reported younger ages at first diet than unaffected co-twins who had dieted. Consistent with previous literature, more twins with AN reported gastrointestinal problems than unaffected co-twins. Although not significant due to low statistical power, more unaffected co-twins reported experiencing emotional neglect than twins with AN. Early dieting may be a harbinger of the development of AN or an early symptom. Higher perfectionism may represent a risk factor, sequela, or both. Sibling perception of neglect is noteworthy given the impact of an ill child with AN on family function and wellbeing. The health and wellbeing of siblings should be addressed clinically when one child in the family suffers from AN.